Deployment of ACT antimalarials for treatment of malaria: challenges and opportunities - Whitty, Christopher JM (BioMed Central, 2008)
Following a long period when the effectiveness of existing mono-therapies for antimalarials was steadily declining with no clear alternative, most malaria-endemic countries in Africa and Asia have adopted artemisinin combination therapy (ACT) as antimalarial drug policy. Several ACT drugs exist and others are in the pipeline. If properly targeted, they have the potential to reduce mortality from malaria substantially. The major challenge now is to get the drugs to the right people. Current evidence suggests that most of those who need the drugs do not get them. Simultaneously, a high proportion of those who are given antimalarials do not in fact have malaria. Financial and other barriers mean that, in many settings, the majority of those with malaria, particularly the poorest, do not access formal healthcare, so the provision of free antimalarials via this route has only limited impact. The higher cost of ACT creates a market for fake drugs. Addressing these problems is now a priority. This review outlines current evidence, possible solutions and research priorities.